Expression of Bcl-2 and epithelial growth factor receptor proteins in keratocystic odontogenic tumor in comparison with dentigerous cyst and ameloblastoma - Seyed Mohammad Razavi; Nakisa Torabinia; Mohammad Reza Mohajeri; Shahriyar Shahriyary; Shirin Ghalegolab; Samin Nouri (Wolters Kluwer Medknow Publications, 2015)
Background: Keratocystic odontogenic tumor (KCOT) is a developmental odontogenic cyst on which various investigations have been focused due to its biological activities, high tendency to recur and different growth mechanisms in comparison with other cystic lesions. Previous studies have shown different biological and proliferative activities for the lining epithelium of KCOT. The aim of this study was immunohistochemical evaluation of Bcl-2 and epidermal growth factor receptor (EGFR) expression in KCOT compared with dentigerous cyst and ameloblastoma. Materials and Methods: Formalin-fixed and paraffin-embedded tissue sections of 16 cases of KCOT, 16 cases of dentigerous cyst and 16 cases of ameloblastoma were immunohistochemically analyzed to determine Bcl-2 and EGFR proteins' expression. Biotin-Stereotavidin method was used. It was observed by two oral pathologists separately, and the data were analyzed by Mann-Whitney and Kruskul-Wallis. P < 0.05 was considered as significant. Results: Regardless of staining intensity, all cases of ameloblastoma and KCOT except dentigerous cases were positively stained for Bcl-2. Expression of Bcl-2 was higher in the peripheral layer of ameloblastoma and basal layer of KCOT. Furthermore, all cases of ameloblastoma and dentigerous cysts except KCOT samples were positively stained for EGFR. Expression of EGFR was higher in the peripheral layer of ameloblastoma and basal layer of dentigerous cysts. Conclusion: According to the expression of - Bcl-2 in ameloblastoma and KCOT, and no expression of EGFR in KCOT, it can be concluded that the biological activity and growth mechanisms of KCOT are different compared with other cystic lesions. However, the aggressive potential of KCOT is not as severe as that of a neoplasm such as ameloblastoma.